Leaders: a comparative analysis of the various leadership styles (Research, Society and Development, 2021)
It is known that organizations within an evolutionary perspective are in constant learning (learning organizations), so they equip of the ability to learn how to properly respond to the particularities of demands, for this reason organizations understand the need to measure its performance. In this segment of learning and adapting to the demand, the image of the leader and leadership styles become one of the main pillars of strategic management. Therefore, the guiding question of this article lies in a comparative analysis of different leadership styles mainly proposed by three authors: Blanchard and Hersey; Warren Bennis (2001) and Jack Welch; and Max Weber (2016). Other authors have also contributed which came to enrich the epistemological matrix of this research. Thus this research was categorized as basic, analytical, qualitative, of exploratory and descriptive nature due to the observation of facts, analysis and interpretation. Information on the bibliography was classified considering its interpretive epistemological approach. Data were capitulated through reflective reading of theme in focus. One has to conclude that operational compliance process does not counterbalance ineffective people; however, operational compliance process does not block effective people. In this antagonism, the employee ceases to be "simply a piece of Taylor," and goes on to add value, once they have the authority over entire system. The combination between effective leaders and operational compliance process is value-adding for the maintenance and growth of organizations.